LITERATUR REVIEW: GAMBARAN POLA ASUH ORANG TUA DALAM PENCEGAHAN STUNTING PADA BALITA DI KOTA KUPANG PROVINSI NUSA TENGGARA TIMUR - Rr Evy Andarini; Dewi Purnamawati (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2023)
Stunting is one of the serious public health problems in Indonesia, including in Kupang City, East Nusa Tenggara Province. Stunting prevention requires an active role from parents or caregivers in providing proper parenting. This study aims to provide an overview of parenting styles that play an important role in stunting prevention in Kupang City, based on a literature review of the latest studies that have been conducted in the Kupang City area. This research uses the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) method through four stages, namely identification, screening, feasibility, and results received. The literature search is done by accessing an online electronic database from Google Scholar. Literature searches have been carried out online in Indonesian-language journals on the Google Scholar database in the last three years (2020-2023). The results showed that the incidence of stunting toddlers in Kupang City was influenced by improper feeding practices due to the low level of knowledge and economy. In addition, various community empowerment activities influence reducing stunting. It is hoped that community empowerment activities will continue to reduce the incidence of stunting in Kupang City.